Chronic inflammatory demyelinating polyneuropathy associated with chronic hepatitis B virus infection - Kabakuş, Nimet; Kansiz, Fatma; Kurt, Neşe Çitak; Aydin, Mustafa; Yoldaş, Tahir (My University, 2004)
Chronic hepatitis B virus infection (HBV) is a disorder that may progress with protean and rare complications. Here, we present a case with chronic inflammatory demyelinating polyneuropathy (CIDP), observed during HBV infection, and stress that CIDP may be associated with HBV infection. A six-year-old boy who had been followed with chronic hepatitis B diagnosis was admitted to our clinic with complaints of chronic progressive weakness and sensorial impairments within the past two months. Neurological examination revealed weakness in distal extremities (0/5) and glove-sock paresthesia. Cerebrospinal fluid protein levels were found to be increased (400 mg/dl). Diagnosis of CIDP was made when a decrease in nerve conductive rate, prolonged distal and F-wave latencies, abnormal temporal dispersion and partial conduction block findings were observed in electromyography. A six-month intravenous immunoglobulin therapy was started and moderate recovery in muscular weakness (3/5) was observed following the first dose. Complete recovery was seen five months after the commencement of the therapy. CIDP may be associated with severe disorders including HBV infection. We suggest that complaints of weakness during chronic HBV infection should be evaluated in terms of CIDP, and such complications should be treated in order to improve the patient's quality of life.
Kronik hepatit B virus enfeksiyonuna eşlik eden kronik enflamatuvar demiyelinizan polinöropati
Keywords: Child; Hepatitis B virus infection; Polyneuropathy